Marco de Buenas Prácticas para la Iniciación y Planeación en Gestión de Proyectos de viviendas de interés social en Corvivienda, Cartagena de Indias D.T y C (2021)
This research contributes to the solution of the evaluation of the management of projects in the Housing Fund for Social Interest and District Urban Reform (Corvivienda), of the city of Cartagena de Indias D.T. and C., determining the level of use and application of techniques and tools in the processes of initiation and planning of projects, identifying their strengths and weaknesses that serve as a starting point for the subsequent improvement of the construction of social housing in managing your projects. It is stated that one of the possible reasons for the non-compliance with the goals in the construction of affordable housing in the programs of the municipal administration of Cartagena de Indias, and a high rate of failed projects in Corvivienda, is due to the low level of application of good practices in project management. Finally, a didactic guide is prepared of the main recommendations to improve the initiation and planning processes of their projects, based on the deficiencies of the project management processes detected in the findings and based on the literary review